Purwarupa Sistem Keamanan Locker Laboratorium Berbasis Raspberry Pi Biometrik dan RFID - Yustina Tritularsih; Yohanes Sugiarto; Hizkia Urianto (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Politeknik Pratama Mulia Surakarta, 2020)
Laboratory is a very crucial place in doing practice learning. Generally, there are high value research equipment and component. It needs completing with electronic security system to improve the security system of laboratory locker user. This research will make a prototype of laboratory locker security system based on Raspberry pi biometrik and RFID. This system combines the fingerprint recognition system with fingerprint sensor R307 and the method of id matching by using RFID Card MIFARE RC522. Raspberry Pi is used as the main controller connected to database MySQL. Integration process with database is successfully done by using Python language as the device connector with database. Data of id tag from the reading result of RFID reader and scanning from sensor of fingerprint on device are successfully delivered to database and sucessfully receive reply response in the form of the user identity which is shown on LCD screen. The process takes less than five seconds as long as the device has been connected with Wifi network. The security lock system of locker box is also equipped with logger data therefore it will make investigation easy if the loss on laboratory equipment happens.